Lived Disablers to Academic Success of the Visually Impaired at the University of Zambia, Sub‑Saharan Africa - Francis Simui; Sophie Kasonde‑Ngandu; Austin M. Cheyeka; Mpine Makoe (Journal of Student Affairs in Africa, 2019)
The World Health Organization’s (WHO) benchmark of persons with disability in every population is 15.6 per cent. However, the University of Zambia is way below that benchmark as it is home to less than 0.1 per cent of students classified as ‘disabled’. Within the 0.1 per cent, students with visual impairment are the majority, estimated at 70 per cent. The purpose of this study was to explore disablers (also known as barriers) to academic success faced by students with visual impairment at the University of Zambia. A Hermeneutic Phenomenological approach directed the research process. Seven purposively sampled participants volunteered to voice their lived experiences and a cluster of themes emerged thereafter. Emerging from their lived experiences are thirteen disablers that impede the learning experiences at University and key amongst them are: (i) negative attitudes; (ii) policypractice disjuncture; (iii) staff unreadiness and unpreparedness; (iv) inaccessible buildings; and (v) rigid curricula.